Study on Muslim friendly spa: a conceptual framework - Jamaluddin, Nor Sabirah Najihah; Mokhtar, Asma'; Hashim, Khairusy Syakirin Has-Yun; Othman, Rashidi; Zainan Nazri, Nurul Jannah; Rosman, Arieff Salleh; Ahmad Fadzillah, Nurrulhidayah (Human Resource Management Academic Research Society, 2018)
Increasing awareness toward healthy lifestyles and pleasant personality attracts people to visit a spa and wellness center, particularly to the career and working women. It is a place that caters to the need for a beauty treatment that can restore, refresh and rejuvenate their body conditions. Spa and wellness center, which offer the products and services according to Shariah principles are often branded as Muslim Friendly spa. It is gaining popularity with the emergence of great numbers of Muslim Friendly spa in certain countries such as Malaysia. However, there is limited study focused on Muslim Friendly Spa since spa and wellness is a new field to be segmented in Muslim Friendly Tourism hospitality and services. Hence, this paper aims to propose a general framework in conceptualizing the characteristics of Muslim Friendly spa and differentiate it with conventional spa. The success of developing Muslim Friendly Spa must be guided by the adoption of Shariah principles, Islamic teaching and values in all aspects of spa operations. From the proposed framework, it will provide an understanding pertaining to the Muslim Friendly spa by exploring the concept together with the elements which enact the industry. In accomplishing this paper, the library research method approach will be employed to evaluate the available resources related to the topic to meet the objective and provide the deliverables. The significance of this paper lies in the fact that it will bring a new dimension to the spa industry, particularly the spa industry players, individuals and business communities to create innovative services for Muslim users. The outcome of this paper will contribute to the body of knowledge and may provide for the expansion studies of implementation Muslim Friendly spa concept.